Evaluasi Penerapan Standar Akuntansi Pemerintahan PP 71 Tahun 2010 Terhadap Belanja Tak Terduga di Masa Pandemi COVID-19 pada Dinas Perindustrian dan Perdagangan Daerah Sulawesi Utara - lengkong, Fetty; Tinangon, Jantje (Universitas Sam Ratulangi, 2022)
Regional Autonomny currently requires Regional Governments to be able to regulate and manage regional finances wisely. In a state of the COVID-19 pandemic, the government must also design in such a way as to be able to make purchases using the Unexpected Expenditure Budget in the APBD which in normal conditions is rarely done. This study aims to evaluate the application of Government Accounting Standards Government Regulation No. 71 of 2010 on Unexpected Expenditures at the Regional Industry and Trade Office of North Sulawesi Province. The research will be carried out using descriptive qualitative methods to describe how the accounting application occurs. The results of the study indicate that the application of accounting is in accordance with PP No. 71 of 2010. For existing financial statements and so on, the Regional Industry and Trade Office of the North Sulawesi Province must always be guided by existing regulations, in order to produce effective regional financial management.